IDENTIFICATION OF WATER QUALITY AT THE REFILL DRINKING WATER DEPOT BUSINESS IN MEDAN HELVETIA AREA USING SIMPLE ADDITIVE WEIGHTING METHOD - Aria Dhanu Tirta; Muhammad Syahputra Novelan; Arpan (INFOKUM, 2022)
The proliferation of refill drinking water businesses among the community has raised doubts about the quality of drinking water from each refilling of drinking water. Especially in the Medan Helvetia area, starting from Pasar 1 to Pasar 7, there are about 23 refill drinking water businesses. This makes the author want to do research on the refill drinking water. Which refill water business has drinking water quality that is good for body health. The author uses the Simple Additive Weighting (SAW) method in calculating research data because this method has been widely used in various studies. The results of the research show that business B in Pasar 2 has good water quality with the highest value from other businesses around Pasar 1 to Pasar 7 Medan Helvetia. it is important to know the quality of drinking water in refilling drinking water so that the health of the community's body